Lack of IL-21 signal attenuates graft-versus-leukemia effect in the absence of CD8 T-cells - Meguro, A (2011)
Previously, we have shown that IL-21R(-/-) splenocytes ameliorate graft-versus-host disease (GVHD) as compared to wild type splenocytes. Here, we investigated whether or not IL-21R(-/-) splenocytes diminish the graft-versus-leukemia (GVL) effect. Surprisingly, IL-21R(-/-) splenocytes efficiently eliminate leukemic cells as well as wild type splenocytes, suggesting the retention of GVL effects in the absence of IL-21 signaling. To compare the GVL effect between IL-21R(-/-) and wild type cells, we titrated the number of splenocytes required for the elimination of leukemic cells and found that the threshold of GVL effect was obtained between 5 × 10(5) and 5 × 10(6) with both types of splenocytes. Co-transplantation with CD8-depleted splenocytes but not with purified CD8 T-cells resulted in a significant reduction in anti-leukemic effect of IL-21R(-/-) cells compared to wild type cells, suggesting that the lack of IL-21 signaling primarily impairs CD4 T-cell rather than CD8 T-cell function and the comparable GVL effect with IL-21R(-/-) bulk splenocytes results from cooperative compensation by CD8 T-cells.